2015
DOI: 10.1080/10590501.2015.1131539
|View full text |Cite
|
Sign up to set email alerts
|

To quit or not: Vulnerability of women to smoking tobacco

Abstract: Tobacco smoking is currently on the rise among women, and can pose a greater health risk. In order to understand the nature of the increase in smoking prevalence among women, we focused on the vulnerability of women to smoking behaviors--smoking cessation or tobacco addiction--and performed a systematic review of the socioeconomic and intrinsic factors as well as tobacco ingredients that affect women's susceptibility to smoking tobacco. We observed that nicotine and other tobacco components including cocoa-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…Some studies have reported that duration of smoking is a much stronger risk factor than amount smoked [17,18,19,20]. Table 4 presents data of genetic frequencies for smokers stratified by smoking duration as a categorical variable (<20 YS/≥20 YS).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that duration of smoking is a much stronger risk factor than amount smoked [17,18,19,20]. Table 4 presents data of genetic frequencies for smokers stratified by smoking duration as a categorical variable (<20 YS/≥20 YS).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested that women tend to evolve from experimentation to addiction more quickly and have greater difficulty in quitting smoking [34,35]. Additionally, they are more susceptible due to hormonal differences [36]. Several studies providing evidence of gender influence on the genetic-smoking relationship are available [9,11,35].…”
Section: Discussionmentioning
confidence: 99%
“…This sex-based difference has been largely attributed to a bene cial protective role of female hormones on the cardiovascular system [16]. Contradictory reports have suggested that smoking women are more prone to develop worse adverse health outcome than smoking men [17]. This has been attributed to the combination of many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and biological factors, hormonal factors, socioeconomic factors, occupational exposure, work stress, personal lifestyle, and secondhand smoke exposure may be responsible for adverse health outcomes in women [18]. This debate occurs along with the rising epidemic of smoking among women, while the prevalence of smoking among men is in slow decline [17].…”
Section: Introductionmentioning
confidence: 99%